Argentina, España, México. Edición pluricéntrica en la obra de Hernán Casciari - Montiel, Daniel Escandell (Diálogos Latinoamericanos, 2013)
The award-winning blognovel Weblog de una mujer gorda by Hernán Casciari was issued in print versions in his home country of Argentina as well as in Spain and Mexico only a few years after its appearance online. Though the three printed texts are rooted in the same online original, significant differences exist among them. In the present article, we analyze these differences with respect to editorial praxis in the three countries, given that what resulted from the print runs can best be described as two distinct books: one for Argentina, and one for Spain and Mexico. While both share events and characters, they diverge in many relevant aspects, not only from each other but also from the original online text. The present analysis seeks to offer an explanation of these changes, basing its analysis in the texts themselves as well as interviews with Casciari.